A survey on the management of overactive bladder by Indonesian urologists (Medical Journal of Indonesia, 2015)
Background: Overactive bladder (OAB) is a clinical syndrome consisting of symptom complex of urgency, with or without incontinence which has significant effects on quality of life and has to be managed properly. The aim of this study was to review the management of OAB by Indonesian urologists.Methods: A self-constructed questionnaires containing diagnostic and treatment options of OAB patients were distributed to Indonesian urologists. This was a cross-sectional study and descriptive analysis method was used to analyze the data.Results: 129 Indonesian urologists participated in this study. Most of them faced more than 20 OAB cases per year with the most common type was OAB without incontinence or dry OAB (57.4%). Most urologists (34.1%) ordered at least three diagnostic tools to determine OAB. They were bladder diary, urinalysis and scoring system. The most used scoring system (48.9%) was the overactive bladder symptoms score (OABSS). Thirty-five point seven percents (35.7%) of urologists used antimuscarinic and behavioral therapy as initial therapy. Solifenacin 5 mg/day was the most common antimuscarinic prescribed as the first line therapy (48%). Most common items commonly evaluated for follow-up: symptoms (96.9%), bladder diary (72.9%); and drugâs side effect (58.1%). When initial therapy had failed, most of the urologists (54.3%) chose to increase the dose of antimuscarinic. None of them chose bladder botulinum toxin injection as their additional therapy.Conclusion: OAB is a frequent disorder which remains a challenge for urologists. The management of patients with OAB by Indonesian urologists has been suitable with the previous studies and guidelines.